Pemberian Soya Yoghurt untuk Wanita Menopause (Soghumen) sebagai Alternatif Makanan Tinggi Kandungan Fitoestrogen: Soya Yogurt to Menopausal Women (Soghumen) as an Alternative to Foods High in Phytoestrogen - Bestari, Astuti Dyah; Suhartini, Linda; Nuraeni, Devi; Alwi, Louis Angel; Angelica, Nadya; Amelia, Sasi Lintang; Putri, Shici Hamaira; Dwi, Evelin Azzahira; An’nida, Firna Asma; Juliyanti, Mila; Anjani, Avira Mutia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Every woman will experience the menopause period in her life. In this period changes occur both physically and psychologically. This is a result of physiological hormonal adaptations, especially estrogen and progesterone. Decreased estrogen levels cause several complaints such as hot flashes, easy body pain, sleep disorders, headaches, dyspareunia, and mood disorders. For this reason, good adaptations are needed to be able to experience the menopause period happily, one of which is consuming foods high in phytoestrogen content. This activity aims to provide education to women regarding physiological changes including common complaints and provide alternative foods high in phytoestrogen content in the form of soybean yoghurt called Soghumen (Soya Yoghurt for Menopause). Education was provided in the form of videos, which were also Soghumen, given to 8 pre-menopausal and menopausal women, then interviews were conducted to assess perceptions of soybean yogurt products. Respondents' perceptions of Soghumen include the taste being considered quite good and almost the same as yogurt products in general, the packaging needs to be adjusted to the texture of the yogurt, namely, it is better to use bottles, other flavors need to be added such as fruit. In general, this product can be accepted by menopausal women as an alternative to foods high in phytoestrogen content. Further research regarding products needs to be carried out in collaboration with nutrition experts.